ta có : x+3/5+x+4/5=x+5/3+x+6/2
=> (x+x)+(3/5+4/4)=(x+x)+(5/3+6/2)
=> 2x+8/5=2x+14/3 ( vô lí )
Ta có: \(x+\frac{3}{5}+x+\frac{4}{4}=x+\frac{5}{3}+x+\frac{6}{2}\)
=> \(x+\frac{3}{5}+x+1=x+\frac{5}{3}+x+3\)
=> \(x+1+x+3=x+\frac{5}{3}-x-\frac{3}{5}\)
=> \(2x+4=\frac{25-9}{15}\)
=> \(2x+4=\frac{16}{15}\)
=> \(2x+4=1+\frac{1}{15}\)
=> \(2x+4-1=\frac{1}{15}\)
=> \(2x+3=\frac{1}{15}\)
=> \(2x=\frac{1}{15}-3\)
=> \(2x=\frac{1-45}{15}\)
=> \(2x=-\frac{44}{15}\)
=> \(x=\frac{\left(-\frac{44}{15}\right)}{2}\)
=> \(x=-\frac{44}{15}.\frac{1}{2}\)
=> \(x=-\frac{22}{15}\)